THEM6‐mediated reprogramming of lipid metabolism supports treatment resistance in prostate cancer. Issue 3 (11th January 2022) - Blomme, Arnaud; Peter, Coralie; Mui, Ernest; Rodriguez Blanco, Giovanny; An, Ning; Mason, Louise M; Jamieson, Lauren E; McGregor, Grace H; Lilla, Sergio; Ntala, Chara; Patel, Rachana; Thiry, Marc; et al.
Abstract: Despite the clinical benefit of androgen‐deprivation therapy (ADT), the majority of patients with advanced prostate cancer (PCa) ultimately develop lethal castration‐resistant prostate cancer (CRPC). In this study, we identified thioesterase superfamily member 6 (THEM6) as a marker of ADT resistance in PCa. THEM6 deletion reduces in vivo tumour growth and restores castration sensitivity in orthograft models of CRPC. Mechanistically, we show that the ER membrane‐associated protein THEM6 regulates intracellular levels of ether lipids and is essential to trigger the induction of the ER stress response (UPR). Consequently, THEM6 loss in CRPC cells significantly alters ER function, reducing de novo sterol biosynthesis and preventing lipid‐mediated activation of ATF4. Finally, we demonstrate that high THEM6 expression is associated with poor survival and correlates with high levels of UPR activation in PCa patients. Altogether, our results highlight THEM6 as a novel driver of therapy resistance in PCa as well as a promising target for the treatment of CRPC. Synopsis: Resistance to androgen‐deprivation therapy (ADT) leads to the development of lethal castration‐resistant prostate cancer. This study highlights THEM6 as a clinically relevant protein that supports ADT‐induced rewiring of lipid metabolism and sustains UPR activation, thus promoting ADT resistance. THEM6 is overexpressed in ADT‐resistant tumours and supports PCa tumour growth in androgen‐deprived conditions. Loss of THEM6 significantly alters the cellular lipidome of CRPC cells, resulting in decreased levels of ether lipids. THEM6 is an ER‐membrane protein that physically interacts with several components of the protein trafficking machinery. Loss of THEM6 significantly affects ER function, reducing de novo sterol synthesis and impairing lipid‐mediated activation of the UPR, two processes that promote ADT resistance. High THEM6 expression in tumour biopsies is associated with shortened patient survival and correlates with sustained UPR activation, thus highlighting the potential of THEM6 as a therapeutic target in CRPC. Abstract : Resistance to androgen‐deprivation therapy (ADT) leads to the development of lethal castration‐resistant prostate cancer. This study highlights THEM6 as a clinically relevant protein that supports ADT‐induced rewiring of lipid metabolism and sustains UPR activation, thus promoting ADT resistance.